Pengaruh Faktor Suku Bunga SBI dan Perubahan Nilai Tukar Rupiah Terhadap Yield Obligasi Korporasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2012 kuartal 1 - 2015 Kuartal 2 - Dewi, Nanda Astriani (Jurnal Ilmiah Mahasiswa FEB, 2016)
The Purpose of this research was to analysis impact of SBI rate and the change of exchange rate to bonds yield corporate which listed in Indonesia Stock Exchange. This research is quantitative research. The data used in this research was secondary data that base on IDX and Bank Indonesia within first quarter in 2012 until second quarter in 2015. Data was processed using panel data with pool regression model. The Result indicate that change of exchange rate and SBI rate have a significant impact with positive sign to bond yield corporateKeyword: yield, exchange rate, suku bunga SBI.